BOOK REVIEW OF BARBARA DAWSON SMITH’S THE ROGUE REPORT - Sari, Ria Arindu (LANTERN (Journal on English Language, Culture and Literature), 2015)
This paperdescribes the strengths and weaknesses of Barbara Dawson Smith’s The Rogue Report. The Rogue Report is a novel which tells about the aristocrat society in London. The writer’s purpose of this review is to explore the strengths and weaknesses by analyzing its intrinsic elements, namely theme, characters, and conflicts. The writer used a library research method and structural approach to analyze the intrinsic elements. In addition, the writer also adopted Erich Fromm’s theory, The Art of Loving to examine the theme of the novel, namely Love. Every novel has its own uniqueness, though The Rogue Report has some weaknesses, it is still a good reading because it has a bunch of value of life.